If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + -1u)(2u + -5) = 0 Reorder the terms: (8 + -1u)(-5 + 2u) = 0 Multiply (8 + -1u) * (-5 + 2u) (8(-5 + 2u) + -1u * (-5 + 2u)) = 0 ((-5 * 8 + 2u * 8) + -1u * (-5 + 2u)) = 0 ((-40 + 16u) + -1u * (-5 + 2u)) = 0 (-40 + 16u + (-5 * -1u + 2u * -1u)) = 0 (-40 + 16u + (5u + -2u2)) = 0 Combine like terms: 16u + 5u = 21u (-40 + 21u + -2u2) = 0 Solving -40 + 21u + -2u2 = 0 Solving for variable 'u'. Factor a trinomial. (-8 + u)(5 + -2u) = 0Subproblem 1
Set the factor '(-8 + u)' equal to zero and attempt to solve: Simplifying -8 + u = 0 Solving -8 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + u = 0 + 8 Combine like terms: -8 + 8 = 0 0 + u = 0 + 8 u = 0 + 8 Combine like terms: 0 + 8 = 8 u = 8 Simplifying u = 8Subproblem 2
Set the factor '(5 + -2u)' equal to zero and attempt to solve: Simplifying 5 + -2u = 0 Solving 5 + -2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2u = 0 + -5 -2u = 0 + -5 Combine like terms: 0 + -5 = -5 -2u = -5 Divide each side by '-2'. u = 2.5 Simplifying u = 2.5Solution
u = {8, 2.5}
| 2y^4-14y^2+2=0 | | -2w+1=-23 | | 10+2m=14 | | 3m+5=-31 | | 9+4w=29 | | (3/4)y=51 | | 5d+12=8d-3 | | 3n+8=41 | | 7t+2=44 | | 10+5m=70 | | 4t+7=27 | | -4b+3=-33 | | 9+5w=69 | | 10n-9=9+4n | | 4w+10=-34 | | -2-4w=26 | | -10-4a=-10 | | 7n-7=28 | | 5k+3=33 | | 6+6x=-66 | | -5m+1=11 | | 4n+8=44 | | 10+7b=59 | | -5w+1=-29 | | 2x+15=6x+7 | | 2x^2=x^2/3+15 | | 7x-12=2+7x | | 3a-8=-8 | | 7+3w=22 | | -4a-7=-43 | | 8-6w=26 | | -1+4d=11 |